PENGARUH KEPUASAN KERJA, KETERLIBATAN KERJA DAN IKLIM ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN PT. SIMPATIK CABANG UNAAHA - Ilham (Jurnal Manajemen Lakidende: Economic & Business, 2020)
This study aims to determine the magnitude of the Effect of Job Satisfaction, Work Engagement and Organizational Climate on Organizational Citizenship Behavior Employees of PT. Sympathetic Unaaha Branch. The population in this study were all employees of PT. Sympathetic Branch of Unaaha, amounting to 38 people, the sample was drawn using saturated sample techniques so that the sample of this study amounted to 38 respondents. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that job satisfaction variables have a positive and significant effect on Organizational Citizenship Behavior, work engagement variables have a positive and significant effect on Organizational Citizenship Behavior, and organizational climate variables have a positive and significant effect on Organizational Citizenship Behavior